Pengaruh Penurunan Kecepatan Elektromotor Untuk Menggerakkan Bowl Separator Terhadap Kinerja Separator Di Pabrik Tapioka PT Hutahaean - A. Sumadi Silitonga; Nelson Silitonga (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
A separator is a mechanical unit that functions to separate cassava starch from water. One tool that plays an important role in the continuity of the separation process in the separator is the electromotor. The electromotor functions as a drive in the separator. The type of electromotor used is usually an induction motor, this is because induction motors have several advantages over other types of motors, including having relatively high efficiency, simple and robust construction, and easy and inexpensive to maintain. One of the disadvantages of an induction motor is that it regulates the rotational speed of the motor. The rotation speed of an induction motor can be adjusted by changing the frequency using an inverter. This study aims to determine the effect of frequency changes on the rotational speed of a 3-phase induction motor using an inverter. The tests were carried out at a frequency of 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz, and 50 Hz. From the research, it can be concluded that the lowest frequency of the induction motor to drive the bowl separator is 25 Hz, and the current will increase if the frequency is lowered.